A dual-responsive anthrapyridone-triazole-based probe for selective detection of Ni2+ and Cu2+: A mimetic system for molecular logic gates based on color change. (March 2020) - Kumar, Ashwani; Chae, Pil Seok; Kumar, Subodh
Abstract: A newly synthesized anthrapyridone-based probe (probe 1 ) with a pyrene-1-triazole unit as a pendant exhibited selective and sensitive detection of Cu 2+ and Ni 2+ among various metal ions. Dramatic color changes were observed for the chromo-fluorogenic probe 1 upon addition of Cu 2+ (yellowish-green to pink) or Ni 2+ (yellowish-green to magenta), enabling naked-eye detection of each metal ion. The limit of detection (LOD) of the probe based on a ratiometric method of determining an absorbance ratio was 0.5 μM for both metal ions. In addition, probe 1 complexed with Ni 2+ (i.e., a [probe 1 + Ni 2+ ]-complex) was alternatively used to detect Cu 2+ with high selectivity and sensitivity (LOD = 0.5 μM). A fluorescence study showed that probe 1 gave rise to green emission, but in the presence of the metal ion, this fluorescence emission was completely (Cu 2+ ) or partially (Ni 2+ ) quenched, resulting in notable LODs of 0.2/0.5 μM (Cu 2+ /Ni 2+ ). Probe 1 therefore possesses a dual responsiveness to the presence of Cu 2+ or Ni 2+ : color change or fluorescence quenching. The combined result with Ni 2+ and Cu 2+ indicates that the anthrapyridone-based probe serves as 'YES, INHIBIT, AND' logic gates. The current system was extensively analyzed by density functional theory calculations, nuclear magnetic resonance, high-resolution mass spectrometry, ultraviolet–visible light, and fluorescence spectroscopies. Graphical abstract: Image 1 Highlights: A new green fluorescent anthrapyridone-based probe 1 was synthesized. A vivid and distinct color change was observed upon addition of Cu 2+ or Ni 2+ to probe 1. Utilizing ratio-metric absorbance changes, we obtained an LOD of 0.5 μM with both metal ions. Fluorescence-based LODs of the probe were 0.5 and 0.2 μM for Ni 2+ and Cu 2+, respectively. NOR, YES, and INHIBIT gates were developed based on the naked-eye color changes.